Summary of Guidelines for Exercise in Pregnancy–are they Comprehensive Enough for Designing the Contents of a Prenatal Exercise Program? - Szumilewicz, Anna; Worska, Aneta; Rajkowska, Natalia; Santos-Rocha, Rita (Current Women's Health Reviews, 2015)
Background: Regular physical activity during pregnancy has a positive effect on the psychophysical condition of the pregnant woman, pregnancy and fetal development, parturition and the postpartum period. However, its level in pregnant women is insufficient in most countries. For an exercise program to be effective it must take into account four training components: intensity, frequency, duration and its content - through a proper selection of the type of exercises and their technique. In this work we aimed to answer the question what information on the contents of prenatal exercises is provided in the current guidelines for exercise during pregnancy in different countries. Methods and Results: We have analyzed 11 documents, that were the official position of national obstetrics, gynecology, or sports medicine institutions from 7 countries. The guidelines provide little information on the contents of prenatal exercise and on the adaptation of sports activities to pregnancy. Conclusions: The guidelines for exercise in pregnancy should be updated based on high-quality research and in collaboration with practitioners in the field of prenatal physical activity, which could increase the chances of their implementation. Trustworthy and comprehensive guidelines created on the basis of international and interdisciplinary initiatives should be disseminated among all interested in prenatal physical activity: pregnant women and their families, obstetrics care providers and exercise professionals to enable them an effective cooperation and to globally promote exercise in pregnancy.
Keywords: exercise program